Strategies to Fund Your Child’s College Education: Using Savings and Tax-Advantaged Vehicles - Jessica McCumber; Jorge Ruiz-Menjivar; Martie Gillen; Sarah M. Ellis (EDIS)
It is never too soon to explore funding options for college educations, whether your child is a newborn or is in middle school. You are more likely to be prepared to fund your child's education if you start planning earlier. This new 4-page document describes and discusses several accounts that allow you to pay for college while taking advantage of tax and savings opportunities. Written by Jessica McCumber, Jorge Ruiz-Menjivar, Martie Gillen, and Sarah M. Ellis, and published by the UF/IFAS Department of Family, Youth and Community Sciences, June 2019.